Keabsahan Penerbitan Sertipikat Tanah Hak Milik Kepada Anak Dibawah Umur: Validity of Freehold Title Issuance to Minor by Land Agency in Bojonegoro - Sudarsono, Leananda Ayu; Istislam; Cahyandari, Dewi (Faculty of Law, Universitas Brawijaya, 2023)
This research aims to analyze property rights certificates issued by the land office based on land law. The land office will issue title certificates number 571 and 671 to minors. Issuance of property rights certificates is carried out in the Complete Systematic Land Registration program, where the applicant is a minor without attaching a guardianship determination letter from the court. This creates legal uncertainty because one of the requirements for carrying out legal actions is being legally competent (adult). Adulthood in the Civil Code is twenty-one years. This research uses normative legal methods to analyze land registration regulations and maturity as well. As a result of the research, the author obtained the result that the issuance of land certificates to minors by the Bojonegoro land office must be considered valid before there is another decision stating otherwise. However, from a procedural perspective, it is not in accordance with statutory regulations and AUPB principles, namely the principle of legal certainty and the principle of accuracy. The legal consequence of issuing a certificate of ownership to a minor by the Bojonegoro land office is that the certificate is valid and valid.